PRINCIPLES OF ARRANGING PHRASEOLOGICAL UNITS IN THE ENTRIES OF RUSSIAN–TURKIC DICTIONARIES - Mavlonova Nargiza Alisherovna (Journals Park Publishing, 2026)
This article presents the principles of arranging phraseological units in the entries of Russian–Turkic dictionaries, illustrated by relevant examples.
Keywords: Phraseological unit, head (key) component, alphabetical arrangement, phraseological dictionary, Russian–Turkic lexicography, phraseography.